Initial characterization of immune microenvironment in pheochromocytoma and paraganglioma - Jin, Bo; Han, Wencong; Guo, Jingjing; Tian, Jie; He, Shiming; Gong, Yanqing; Zhou, Jingcheng; He, Qun; Shen, Qi; Zhang, Zheng (Frontiers in Genetics, 2022)
Currently, immunotherapy has been widely used to treat a variety of advanced solid tumors due to fewer adverse effects, faster onset of action, and longer durable responses compared to chemotherapy. Besides, immunotherapy can improve the autoimmune status, thus allowing patients to benefit from the treatment in the long term. Here, using fluorescent PCR-capillary electrophoresis and immunohistochemistry, we analyzed the characteristics of the immune microenvironment in pheochromocytoma and paraganglioma (PPGL), providing a scientific reference for further mechanistic studies of the development of PPGL. PD-L1 is sparely expressed in PPGL with low positive rates and low expression levels, which is not correlated with tumor malignancy. Moreover, the number of cases positive for intratumoral CD4+ and CD8+ lymphocyte infiltration is extremely low. As such, the immune microenvironment in PPGL may be in “immune desertification” or “immune rejection” states in which the infiltration of CD4+ and CD8+ lymphocytes is prevented, rendering immunotherapy less effective. In sum, our results suggest that PPGL is a microsatellite stable tumor with low tumor mutational burden (TMB) levels, weak ability to produce neoantigens, and poor tumor antigenicity.